A carbon-based composite material for sodium ion battery and a preparation method thereof
By preparing carbon-based composite materials with columnar cavity support, the problem of low service life of sodium ion batteries is solved, efficient sodium ion storage and battery stability are achieved, and the recycling life of the battery is extended.
Patent Information
- Application Number
- CN202310270505.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-03-20
AI Technical Summary
The service life of sodium ion batteries is low, and the radius and mass of sodium ions are large, resulting in lower energy density than that of lithium ion batteries, and causing deformation of the electrode material during charging and discharging, affecting stability.
Using a preparation method of a carbon-based composite material for sodium ion batteries, a phenolic resin glue with amino side chains is formed by reacting phenol, p-aminophenol and aqueous formaldehyde solution, and reacting with reinforced prepolymer and carbon-based support to form a resin coating. The carbon-based material is then formed by carbonization to form a composite material with columnar cavity support, which can compress the cavity during sodium ion expansion, counteract material expansion, and increase sodium storage performance and battery life.
It significantly improves the service life and sodium storage capacity of sodium ion batteries, extends the battery's cycle life, and maintains efficient battery performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery preparation, and in particular to a carbon-based composite material for a sodium ion battery and a preparation method thereof. Background Art
[0002] Sodium-ion batteries are "rocking-chair batteries". During the charging process, sodium ions are released from the positive electrode material, releasing electrons at the same time. Sodium ions enter the electrolyte, pass through the diaphragm, diffuse to the negative electrode, and then embed into the active material. The positive electrode active material loses electrons, and the potential gradually increases; the negative electrode active material becomes sodium-rich, the potential gradually decreases, and the battery voltage increases overall. Electrons are transferred from the positive electrode to the negative electrode through the external circuit, participating in the oxidation reaction of the positive electrode and the reduction reaction of the negative electrode. During the discharge process, sodium ions are released from the negative electrode material, diffuse through the electrolyte through the diaphragm to the positive electrode, and the same number of electrons are transferred from the positive electrode to the negative electrode through the external circuit load. The positive electrode potential gradually decreases, the negative electrode potential gradually increases, and the battery voltage as a whole decreases. However, since the radius (about 0.102nm) and mass (22.99g / mol) of sodium ions are much larger than the radius (about 0.076nm) and mass (6.94g / mol) of lithium ions, the energy density of sodium ion batteries is lower than that of corresponding lithium ion batteries, and the insertion and extraction of sodium ions during the charge and discharge process will cause large deformation of the electrode material and affect its stability. Summary of the invention
[0003] The purpose of the present invention is to provide a carbon-based composite material for a sodium ion battery and a preparation method thereof, so as to solve the problem of low service life of sodium ion batteries at this stage.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a carbon-based composite material for a sodium ion battery comprises the following steps:
[0006] Step S1: Phenol, p-aminophenol, deionized water and formaldehyde aqueous solution are mixed evenly, and barium hydroxide is added under stirring at a speed of 150-200 r / min and a temperature of 70-75° C. After the addition is completed, the temperature is raised to 93-95° C. and kept warm for 1-2 hours, and an equal amount of formaldehyde aqueous solution is added, and the reaction is continued for 30-40 minutes to obtain a resin glue;
[0007] Step S2: The resin glue, the reinforced prepolymer, the carbon-based carrier and tetrahydrofuran are mixed evenly, stirred for 5-7 hours at a rotation speed of 600-800 r / min and a temperature of 50-60° C., the temperature is raised to 180-190° C., and after heat preservation for 3-4 hours, the temperature is raised to 1500-1550° C. and calcined for 2-3 hours to obtain a composite material.
[0008] Furthermore, the mass ratio of phenol, p-aminophenol, deionized water, formaldehyde aqueous solution, and barium hydroxide described in step S1 is 9:1:10:20:1.25, and the mass fraction of the formaldehyde aqueous solution is 35%.
[0009] Furthermore, the molar ratio of the amino groups on the resin glue, the isocyanate groups on the reinforced prepolymer, and the amino groups on the carbon-based carrier in step S2 is 1:2:1.
[0010] Further, the reinforced prepolymer is prepared by the following steps:
[0011] Step A1: potassium carbonate, deionized water and tetrahydrofuran are mixed uniformly, and phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane are added under stirring at a speed of 500-800 r / min and a temperature of 20-25° C. After stirring for 7-9 days, dichloromethane is added and allowed to stand for stratification, the water layer is removed, and the dichloromethane is distilled from the organic layer to obtain a modifier;
[0012] Step A2: polytetramethylene glycol-2000, toluene diisocyanate, a modifier and tetrahydrofuran are mixed, and reacted for 2-3 hours at a rotation speed of 200-300 r / min and a temperature of 80-85° C. to obtain a reinforced prepolymer.
[0013] Furthermore, the usage ratio of potassium carbonate, deionized water, tetrahydrofuran, phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane described in step A1 is 0.04g:10mL:100mL:15.86g:5.29g.
[0014] Furthermore, the molar ratio of polytetramethylene ether glycol-2000, toluene diisocyanate and modifier described in step A2 is 1:4:2.
[0015] Further, the carbon-based carrier is prepared by the following steps:
[0016] Step B1: Sodium lignin sulfonate, PVA1788 and deionized water are mixed, stirred for 15-20 minutes at a speed of 150-200 r / min, ammonia water is added, stirred for 10-15 minutes, formaldehyde aqueous solution is added, the temperature is raised to 45-50°C, and the temperature is kept for 20-25 hours, the temperature is raised to 95-100°C, and the temperature is kept for 18-22 hours, 1,4-butanediol diglycidyl ether is added, and the temperature is kept for 10-12 hours to obtain a resin liquid, the resin liquid is added to a hydrothermal reactor, and the temperature is kept at 200-220°C for 10-15 hours, the filtrate is removed by filtering, and the substrate is roasted at a temperature of 550-600°C for 2-3 hours to obtain porous carbon;
[0017] Step B2: dissolve sodium molybdate dihydrate in deionized water, keep the pH value at 6, stir and add thiourea at a speed of 200-300 r / min, stir for 30-40 minutes, add porous carbon, continue stirring for 1-1.5 hours, keep warm for 20-25 hours at a temperature of 240-260°C to obtain a composite carrier, disperse the composite carrier in deionized water, stir and add KH550 dropwise at a speed of 150-200 r / min and a temperature of 30-40°C, stir for 1-1.5 hours, filter and dry to obtain a carbon-based carrier.
[0018] Furthermore, the dosage ratio of sodium lignin sulfonate, PVA1788, deionized water, ammonia water, formaldehyde aqueous solution and 1,4-butanediol diglycidyl ether described in step B1 is 4g:2g:500mL:2.5g:7mL:2g, and the mass fraction of formaldehyde aqueous solution is 35%.
[0019] Furthermore, the dosage ratio of sodium molybdate dihydrate, deionized water, thiourea and porous carbon in step B2 is 6g:80mL:16g:5g, and the dosage of KH550 is 5-8% of the mass of the composite carrier.
[0020] Beneficial effects of the present invention: A carbon-based composite material for sodium ion batteries prepared by the present invention is prepared by reacting phenol, p-aminophenol and formaldehyde aqueous solution to form a phenolic resin glue with an amino side chain, reacting the resin glue, a reinforcing prepolymer and a carbon-based carrier so that the amino groups on the resin glue and the amino groups on the carbon-based carrier react with the polyurethane at both ends of the reinforcing prepolymer respectively to form a resin-coated carbon-based material, and further carbonizing so that the surface resin is carbonized to obtain a composite material, the reinforcing prepolymer is made of phenyl methoxy silane and 3-aminopropyl trimethoxy silane as raw materials, hydrolyzed and polymerized to form a cage-type polysilsesquioxane with amino and phenyl side chains to obtain a modifier, the modifier, polytetramethylene ether glycol-2000 and toluene diisocyanate are reacted, and the reinforcing prepolymer is obtained by controlling the dosage, the carbon-based carrier is made of sodium lignin sulfonate as a raw material and reacts with formaldehyde to form a lignin-based phenolic resin, A resin is obtained, and the resin liquid is subjected to hydrothermal treatment and then carbonized to obtain porous carbon. Sodium molybdate dihydrate is dissolved in water and added to porous carbon, and a large amount of three-dimensional spherical molybdenum disulfide is loaded on the porous carbon to obtain a composite carrier. The composite carrier is then treated with KH550 to graft a large amount of active amino groups on the surface to obtain a carbon-based carrier. When the resin glue, the reinforced prepolymer and the carbon-based carrier are reacted and carbonized, a columnar cavity support is formed between the resin layer and the carbon-based carrier. Due to the radius of sodium ions, the volume of the material will expand. During the expansion process, the cavity will be compressed, and the cavity can be slightly deformed, so that the force generated by the expansion is offset, and the volume expansion of the carbon-based carrier is effectively prevented, thereby restoring the volume of the carbon-based carrier. At the same time, the internal cavity can increase the sodium storage performance and the sodium storage capacity is large, so that the battery will not have performance degradation after repeated use, which greatly increases the service life of the battery. Implementation
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0022] A method for preparing a carbon-based composite material for a sodium ion battery comprises the following steps:
[0023] Step S1: Phenol, p-aminophenol, deionized water and formaldehyde aqueous solution are mixed evenly, and barium hydroxide is added under stirring at a speed of 150 r / min and a temperature of 70° C. After the addition is completed, the temperature is raised to 93° C. and kept warm for 1 hour, and an equal amount of formaldehyde aqueous solution is added, and the reaction is continued for 30 minutes to obtain a resin glue;
[0024] Step S2: The resin glue, the reinforcing prepolymer, the carbon-based carrier and tetrahydrofuran are mixed evenly, stirred for 5 hours at a speed of 600 r / min and a temperature of 50° C., the temperature is raised to 180° C., and after heat preservation for 3 hours, the temperature is raised to 1500° C. and calcined to obtain a composite material.
[0025] The mass ratio of phenol, p-aminophenol, deionized water, formaldehyde aqueous solution and barium hydroxide described in step S1 is 9:1:10:20:1.25, and the mass fraction of formaldehyde aqueous solution is 35%.
[0026] The molar ratio of the amino groups on the resin glue, the isocyanate groups on the reinforced prepolymer, and the amino groups on the carbon-based carrier described in step S2 is 1:2:1.
[0027] The reinforced prepolymer is prepared by the following steps:
[0028] Step A1: potassium carbonate, deionized water and tetrahydrofuran are mixed uniformly, and phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane are added under stirring at a speed of 500 r / min and a temperature of 20° C. After stirring for 7 days, dichloromethane is added and allowed to stand for stratification, the water layer is removed, and the dichloromethane is distilled from the organic layer to obtain a modifier;
[0029] Step A2: polytetramethylene glycol-2000, toluene diisocyanate, a modifier and tetrahydrofuran are mixed, and reacted at a speed of 200 r / min and a temperature of 80° C. for 2 hours to obtain a reinforced prepolymer.
[0030] The amount ratio of potassium carbonate, deionized water, tetrahydrofuran, phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane described in step A1 is 0.04g:10mL:100mL:15.86g:5.29g.
[0031] The molar ratio of polytetramethylene glycol-2000, toluene diisocyanate and modifier described in step A2 is 1:4:2.
[0032] The carbon-based carrier is prepared by the following steps:
[0033] Step B1: Sodium lignin sulfonate, PVA1788 and deionized water are mixed, stirred for 15 minutes at a speed of 150 r / min, ammonia water is added, stirred for 10 minutes, formaldehyde aqueous solution is added, the temperature is raised to 45°C, and the temperature is kept for 20 hours, the temperature is raised to 95°C, and the temperature is kept for 18 hours, 1,4-butanediol diglycidyl ether is added, and the temperature is kept for 10 hours to obtain a resin liquid, the resin liquid is added to a hydrothermal reactor, and the temperature is kept at 200°C for 10 hours, the filtrate is removed by filtration, and the substrate is calcined at 550°C for 2 hours to obtain porous carbon;
[0034] Step B2: Dissolve sodium molybdate dihydrate in deionized water, maintain the pH value at 6, stir and add thiourea at a speed of 200-300 r / min, stir for 30 minutes, add porous carbon, continue stirring for 1 hour, keep warm at 240°C for 20 hours to obtain a composite carrier, disperse the composite carrier in deionized water, stir and add KH550 dropwise at a speed of 150 r / min and a temperature of 30°C, stir for 1 hour, filter and dry to obtain a carbon-based carrier.
[0035] The dosage ratio of sodium lignin sulfonate, PVA1788, deionized water, ammonia water, formaldehyde aqueous solution and 1,4-butanediol diglycidyl ether described in step B1 is 4g:2g:500mL:2.5g:7mL:2g, and the mass fraction of formaldehyde aqueous solution is 35%.
[0036] The dosage ratio of sodium molybdate dihydrate, deionized water, thiourea and porous carbon described in step B2 is 6g:80mL:16g:5g, and the dosage of KH550 is 5% of the mass of the composite carrier. Example
[0037] A method for preparing a carbon-based composite material for a sodium ion battery comprises the following steps:
[0038] Step S1: Phenol, p-aminophenol, deionized water and formaldehyde aqueous solution are mixed evenly, and barium hydroxide is added under stirring at a speed of 180 r / min and a temperature of 73° C. After the addition is completed, the temperature is raised to 94° C. and kept warm for 1.5 hours, and an equal amount of formaldehyde aqueous solution is added, and the reaction is continued for 35 minutes to obtain a resin glue;
[0039] Step S2: The resin glue, the reinforced prepolymer, the carbon-based carrier and tetrahydrofuran are mixed evenly, stirred for 6 hours at a speed of 600 r / min and a temperature of 55° C., the temperature is raised to 185° C., and after heat preservation for 3.5 hours, the temperature is raised to 1530° C. and calcined to obtain a composite material.
[0040] The mass ratio of phenol, p-aminophenol, deionized water, formaldehyde aqueous solution and barium hydroxide described in step S1 is 9:1:10:20:1.25, and the mass fraction of formaldehyde aqueous solution is 35%.
[0041] The molar ratio of the amino groups on the resin glue, the isocyanate groups on the reinforced prepolymer, and the amino groups on the carbon-based carrier described in step S2 is 1:2:1.
[0042] The reinforced prepolymer is prepared by the following steps:
[0043] Step A1: potassium carbonate, deionized water and tetrahydrofuran are mixed uniformly, and phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane are added under stirring at a speed of 500 r / min and a temperature of 25° C. After stirring for 8 days, dichloromethane is added and allowed to stand for stratification, the water layer is removed, and the dichloromethane is distilled from the organic layer to obtain a modifier;
[0044] Step A2: polytetramethylene glycol-2000, toluene diisocyanate, a modifier and tetrahydrofuran are mixed, and reacted at a speed of 200 r / min and a temperature of 85° C. for 2.5 hours to obtain a reinforced prepolymer.
[0045] The amount ratio of potassium carbonate, deionized water, tetrahydrofuran, phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane described in step A1 is 0.04g:10mL:100mL:15.86g:5.29g.
[0046] The molar ratio of polytetramethylene glycol-2000, toluene diisocyanate and modifier described in step A2 is 1:4:2.
[0047] The carbon-based carrier is prepared by the following steps:
[0048] Step B1: Sodium lignin sulfonate, PVA1788 and deionized water are mixed, stirred for 15 minutes at a speed of 180 r / min, ammonia water is added, stirred for 15 minutes, formaldehyde aqueous solution is added, the temperature is raised to 50°C, and the temperature is kept for 25 hours, the temperature is raised to 98°C, and the temperature is kept for 20 hours, 1,4-butanediol diglycidyl ether is added, and the temperature is kept for 12 hours to obtain a resin liquid, the resin liquid is added to a hydrothermal reactor, and the temperature is kept for 15 hours at 210°C, the filtrate is removed by filtration, and the substrate is calcined at 580°C for 2 hours to obtain porous carbon;
[0049] Step B2: Dissolve sodium molybdate dihydrate in deionized water, maintain the pH value at 6, stir and add thiourea at a speed of 300 r / min, stir for 35 minutes, add porous carbon, continue stirring for 1.5 hours, keep warm for 25 hours at a temperature of 250°C to obtain a composite carrier, disperse the composite carrier in deionized water, stir and add KH550 dropwise at a speed of 180 r / min and a temperature of 35°C, stir for 1 hour, filter and dry to obtain a carbon-based carrier.
[0050] The dosage ratio of sodium lignin sulfonate, PVA1788, deionized water, ammonia water, formaldehyde aqueous solution and 1,4-butanediol diglycidyl ether described in step B1 is 4g:2g:500mL:2.5g:7mL:2g, and the mass fraction of formaldehyde aqueous solution is 35%.
[0051] The dosage ratio of sodium molybdate dihydrate, deionized water, thiourea and porous carbon described in step B2 is 6g:80mL:16g:5g, and the dosage of KH550 is 6% of the mass of the composite carrier. Example
[0052] A method for preparing a carbon-based composite material for a sodium ion battery comprises the following steps:
[0053] Step S1: Phenol, p-aminophenol, deionized water and formaldehyde aqueous solution are mixed evenly, and barium hydroxide is added under stirring at a speed of 200 r / min and a temperature of 75° C. After the addition is completed, the temperature is raised to 95° C. and kept warm for 2 hours, and an equal amount of formaldehyde aqueous solution is added, and the reaction is continued for 40 minutes to obtain a resin glue;
[0054] Step S2: The resin glue, the reinforced prepolymer, the carbon-based carrier and tetrahydrofuran are mixed evenly, stirred for 7 hours at a speed of 800 r / min and a temperature of 60° C., the temperature is raised to 190° C., and after heat preservation for 4 hours, the temperature is raised to 1550° C. and calcined to obtain a composite material.
[0055] The mass ratio of phenol, p-aminophenol, deionized water, formaldehyde aqueous solution and barium hydroxide described in step S1 is 9:1:10:20:1.25, and the mass fraction of formaldehyde aqueous solution is 35%.
[0056] The molar ratio of the amino groups on the resin glue, the isocyanate groups on the reinforced prepolymer, and the amino groups on the carbon-based carrier described in step S2 is 1:2:1.
[0057] The reinforced prepolymer is prepared by the following steps:
[0058] Step A1: potassium carbonate, deionized water and tetrahydrofuran are mixed uniformly, and phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane are added under stirring at a speed of 800 r / min and a temperature of 25° C. After stirring for 9 days, dichloromethane is added and allowed to stand for stratification, the water layer is removed, and the dichloromethane is distilled from the organic layer to obtain a modifier;
[0059] Step A2: polytetramethylene glycol-2000, toluene diisocyanate, a modifier and tetrahydrofuran are mixed, and reacted at a speed of 300 r / min and a temperature of 85° C. for 3 hours to obtain a reinforced prepolymer.
[0060] The amount ratio of potassium carbonate, deionized water, tetrahydrofuran, phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane described in step A1 is 0.04g:10mL:100mL:15.86g:5.29g.
[0061] The molar ratio of polytetramethylene glycol-2000, toluene diisocyanate and modifier described in step A2 is 1:4:2.
[0062] The carbon-based carrier is prepared by the following steps:
[0063] Step B1: Sodium lignin sulfonate, PVA1788 and deionized water are mixed, stirred for 20 minutes at a speed of 200 r / min, ammonia water is added, stirred for 15 minutes, formaldehyde aqueous solution is added, the temperature is raised to 45-50°C, and the temperature is kept for 25 hours, the temperature is raised to 100°C, and the temperature is kept for 22 hours, 1,4-butanediol diglycidyl ether is added, and the temperature is kept for 12 hours to obtain a resin liquid, the resin liquid is added to a hydrothermal reactor, and the temperature is kept for 15 hours at 220°C, the filtrate is filtered to remove the filtrate, and the substrate is calcined at 600°C for 3 hours to obtain porous carbon;
[0064] Step B2: Dissolve sodium molybdate dihydrate in deionized water, maintain the pH value at 6, stir and add thiourea at a speed of 300 r / min, stir for 40 minutes, add porous carbon, continue stirring for 1.5 hours, keep warm for 25 hours at a temperature of 260°C to obtain a composite carrier, disperse the composite carrier in deionized water, stir and add KH550 dropwise at a speed of 200 r / min and a temperature of 40°C, stir for 1.5 hours, filter and dry to obtain a carbon-based carrier.
[0065] The dosage ratio of sodium lignin sulfonate, PVA1788, deionized water, ammonia water, formaldehyde aqueous solution and 1,4-butanediol diglycidyl ether described in step B1 is 4g:2g:500mL:2.5g:7mL:2g, and the mass fraction of formaldehyde aqueous solution is 35%.
[0066] The dosage ratio of sodium molybdate dihydrate, deionized water, thiourea and porous carbon described in step B2 is 6g:80mL:16g:5g, and the dosage of KH550 is 8% of the mass of the composite carrier.
[0067] Comparative Example 1
[0068] Compared with Example 1, this comparative example directly uses a carbon-based carrier as the carbon-based composite material.
[0069] Comparative Example 2
[0070] Compared with Example 1, this comparative example is prepared by the following steps: dissolving sodium molybdate dihydrate in deionized water, maintaining the pH value at 6, stirring and adding thiourea at a rotation speed of 200-300 r / min, stirring for 30 minutes, adding graphene oxide, continuing to stir for 1 hour, and heat-treating at a temperature of 240°C for 20 hours to obtain a carbon-based composite material.
[0071] The carbon-based composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were respectively ground into carbon-based composite materials, polyvinylidene fluoride and carbon black in a mass ratio of 8:1:1 for 1 hour, and then NMP was added and stirred evenly to prepare a slurry, which was then coated on a homogeneous copper foil, and then vacuum dried for 10 hours at a temperature of 80°C, and then cut into circular electrode sheets with a diameter of 14 mm. The loading amount of the carbon-based composite material on the electrode sheet was 3 mg / cm 2 The battery shell type selected is CR2032, the battery electrode is made of processed pure sodium sheet, the battery separator is made of glass fiber, the electrolyte is 1MNaPF6-EC / DMC solution with a volume ratio of 1:1, and the battery sample is made.
[0072] The battery sample was discharged at a constant current of 0.05C to 0.005V, and the obtained capacity was recorded as the 0.05C charging capacity; then it was allowed to stand for 5 minutes, and charged at a constant current of 0.1C to a voltage of 3.0V, and the obtained capacity was recorded as the 0.1C discharge capacity; finally, the operation was stopped, and the first coulomb efficiency was 0.05C charging capacity / 0.1C discharge capacity.
[0073] Discharge to 0.005V at 0.1C constant current, let stand for 5 minutes, then charge to 3.0V at 0.1C constant current; then let stand for 5 minutes, then discharge to 0.005V at 0.1C constant current, the obtained capacity is the discharge capacity corresponding to 0.1C; finally stop running and record the second discharge capacity as the discharge capacity corresponding to 0.1C.
[0074] Discharge to 0.005V at 0.2C constant current, let stand for 5 minutes, then charge to 3.0V at 0.2C constant current; then let stand for 5 minutes, then discharge to 0.005V at 0.2C constant current, the obtained capacity is the discharge capacity corresponding to 0.2C; finally stop running and record the second discharge capacity as the discharge capacity corresponding to 0.2C.
[0075] Discharge at 0.2C constant current to 0.005V, let stand for 5 minutes, then charge at 0.2C constant current to 3.0V; cycle 100 times, 500 times and 800 times in sequence, record the discharge capacity, calculate the capacity retention rate, and the test results are shown in the following table;
[0076]
[0077] It can be seen from the above table that the first coulombic efficiency of the battery made of the carbon-based composite material obtained in Examples 1-3 is 98.26-98.35%, the 0.1C discharge capacity is 432.8-441.5 mAh / g, the 0.2 discharge capacity is 429.6-438.2 mAh / g, the capacity retention rate after 100 cycles is 99.1-99.5%, the capacity retention rate after 500 cycles is 98.3-98.5%, and the capacity retention rate after 800 cycles is 92.5-93.4%, indicating that the present invention has good sodium ion capacity and a long battery life.
[0078] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a carbon-based composite material for a sodium ion battery, characterized in that: The specific steps include: Step S1: mixing phenol, p-aminophenol, deionized water and formaldehyde aqueous solution and adding barium hydroxide, after the addition is complete, heating and maintaining the temperature, adding an equal mass of formaldehyde aqueous solution, and continuing the reaction to obtain a resin glue; Step S2: mixing and stirring the resin glue, the reinforced prepolymer, the carbon-based carrier and tetrahydrofuran, heating and preserving the mixture, and then heating and calcining the mixture to obtain a composite material; The reinforced prepolymer is prepared by the following steps: Step A1: potassium carbonate, deionized water and tetrahydrofuran are mixed and stirred, and phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane are added. After stirring, dichloromethane is added and allowed to stand for stratification, the water layer is removed, and the dichloromethane is distilled from the organic layer to obtain a modifier; Step A2: mixing polytetramethylene glycol-2000, toluene diisocyanate, a modifier and tetrahydrofuran to obtain a reinforced prepolymer; The carbon-based carrier is prepared by the following steps: Step B1: Sodium lignin sulfonate, PVA1788 and deionized water are mixed and stirred, ammonia water is added, stirred, formaldehyde aqueous solution is added, the temperature is increased and kept warm, the temperature is increased and kept warm, 1,4-butanediol diglycidyl ether is added, and the temperature is kept warm to obtain a resin liquid, the resin liquid is added to a hydrothermal reactor, kept warm, the filtrate is removed by filtering, and the substrate is roasted to obtain a porous carbon; Step B2: dissolve sodium molybdate dihydrate in deionized water, keep it acidic, stir and add thiourea, stir, add porous carbon, continue stirring, and keep warm to obtain a composite carrier. Disperse the composite carrier in deionized water, stir and add KH550 dropwise, stir, filter and dry to obtain a carbon-based carrier.
2. The method for preparing a carbon-based composite material for a sodium ion battery according to claim 1, characterized in that: The mass ratio of phenol, p-aminophenol, deionized water, formaldehyde solution and barium hydroxide described in step S1 is 9:1:10:20:1.
25.
3. The method for preparing a carbon-based composite material for sodium ion batteries according to claim 1, characterized in that: The molar ratio of the amino groups on the resin glue, the isocyanate groups on the reinforced prepolymer, and the amino groups on the carbon-based carrier described in step S2 is 1:2:
1.
4. The method for preparing a carbon-based composite material for a sodium ion battery according to claim 1, characterized in that: The amount ratio of potassium carbonate, deionized water, tetrahydrofuran, phenyltrimethoxysilane and 3-aminopropyltrimethoxysilane described in step A1 is 0.04g:10mL:100mL:15.86g:5.29g.
5. The method for preparing a carbon-based composite material for sodium ion battery according to claim 1, characterized in that: The molar ratio of polytetramethylene glycol-2000, toluene diisocyanate and modifier described in step A2 is 1:4:
2.
6. The method for preparing a carbon-based composite material for sodium ion batteries according to claim 1, characterized in that: The amount ratio of sodium lignin sulfonate, PVA1788, deionized water, ammonia water, formaldehyde aqueous solution and 1,4-butanediol diglycidyl ether described in step B1 is 4g:2g:500mL:2.5g:7mL:2g.
7. The method for preparing a carbon-based composite material for sodium ion batteries according to claim 1, characterized in that: The dosage ratio of sodium molybdate dihydrate, deionized water, thiourea and porous carbon described in step B2 is 6g:80mL:16g:5g, and the dosage of KH550 is 5-8% of the mass of the composite carrier.
8. A carbon-based composite material for sodium ion batteries, characterized in that: Prepared according to any one of claims 1 to 7.